Uptake mechanisms of cell-internalizing nucleic acid aptamers for applications as pharmacological agents. Issue 10 (5th August 2021) - Alamudi, Samira Husen; Kimoto, Michiko; Hirao, Ichiro
Abstract : Selection methods in generating cell-internalizing nucleic acid aptamer via cell-SELEX technique for applications in diagnostics and therapeutics are discussed. Their challenges, optimization strategies and cellular uptake mechanisms are presented. Abstract : Nucleic acid aptamers, also regarded as chemical antibodies, show potential as targeted therapeutic and delivery agents since they possess unique advantages over antibodies. Generated by an iterative selection and amplification process from oligonucleotide libraries using cultured cells, the aptamers bind to their target molecules expressed on the cell surface. Excitingly, most aptamers also demonstrate a cell-internalizing property in native living cells, allowing them to directly enter the cells via endocytosis depending on the target. In this review, we discuss selection methods in generating cell-internalizing aptamers via a cell-based selection process, along with their challenges and optimization strategies. We highlight the cellular uptake routes adopted by the aptamers and also their intracellular fate after the uptake, to give an overview of their mechanism of action for applications as promising pharmacological agents.